Do epistemicídio à (in)visibilidade étnica dos ciganos Calons no Brasil/Bahia - Silva, Irandir (2021)
This article is the result of theoretical discussions based on some authors – such as Hall (2003), Boaventura dos Santos (2010), Giannella (2015), among others – debated in the curricular component of Research Epistemology, attended in the second quarter of 2020.2, linked to the State and Society Doctoral Program of the Federal University of Southern Bahia (UFSB). The doctoral research mentioned is a result of concerns arising from investigations initiated in the master's program, in the period 2007/2010, at PPGEduC/UNEB-Ba. The choice of the Gypsy theme is justified by the fact that I grew up hearing from Gypsy calon friends how much they were discriminated against and disrespected by non-Gypsies, for having their cultural values and way of living different considering those existing in society. The objective of this study is to make a brief presentation on the gypsy epistemicide that occurred in Portugal and extended to Brazil from the colonial period to the present time, including the prejudices and abandonment of communities in the current pandemic outbreak of Covid-19.